Kajian Jalur Evakuasi Kebakaran Terhadap Keamanan Pengguna pada Gedung: Studi Kasus Rumah Susun Gebang Raya - Galang Arya Yudha; Ade Syoufa (Jurnal Arsitektur Wastu Padma, 2024)
Building safety is a form of building reliability against disasters, one of which is fire hazard. In Indonesia, there are still many buildings that do not apply this security. In this research, the case study taken is the Gebang Raya block A flat, Tangerang City. This research is aimed at identifying the completeness of evacuation facilities based on standardization and also knowing the equipment and placement of active fire protection equipment in Gebang Raya block A flats. The research method used is descriptive qualitative by conducting field observations, interviews, documentation and literature review to obtain information about fire evacuation facilities, standardization of fire evacuation facilities, and equipment and placement of active fire protection systems in the flats. From the results of the discussion, it can be stated that the Gebang Raya block A flats in terms of completeness are not in accordance with existing standards and regulations. In terms of standardization that Gebang Raya block A flats still have fire evacuation facilities, especially emergency stairs that do not meet the standards both based on theory and existing regulations. In terms of completeness, the active fire protection system in this flat does not meet. There is only a standpipe and slang pipe system and a light fire extinguisher.